High-Resolution Melting Approach to Efficient Identification and Quantification of H275Y Mutant Influenza H1N1/2009 Virus in Mixed-Virus-Population Samples - Lee, Hong Kai; Lee, Chun Kiat; Loh, Tze Ping; Tang, Julian Wei-Tze; Tambyah, Paul Anantharajah; Koay, Evelyn Siew-Chuan (Journal of Clinical Microbiology, 2011)
Article Usage Stats Services JCM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JCM About JCM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JCM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0095-1137 Online ISSN: 1098-660X Copyright © 2014 by the American Society for Microbiology. For an alternate route to JCM .asm.org, visit: JCM